Avaliação da liberação de bisfenol A em blocos de materiais dentários para CAD/CAM - Carvalho, Ligia Maria Nogarett Pibernat de (2017)
The aim of the present study was to asses the present of Bisphenol A in dental material used on CAD/CAM block.For this In Vitro study, blocks for CAD-CAM, Lava Ultimate, Enamic and Mark II in standardized fragments containeing Bisphenol A were evaluated. Ten fragments of each block were made: n = 30, immersed in deionized water on group 1 and artificial saliva Kin Hidrat on group 2 in a light protected bottle.Stored in a culture stove for 24 hours, all samples were put in 1,5ml bottles containing 1,0ml of artificial saliva (KIN HIDRAT, PharmaKIN, São Paulo, Brazil ) on group 1 and deionized water on group 2, and then freezed in -80ºC for 24 hours. After the 24 hour period, the samples were submitted to High Efficiency Chromatography on Toxicology and Pharmacology Institute of PUCRS as methodology described on this study.After cromatographic analysis of groups 1 and 2, the non-release of Bisphenol A was observed in all groups of samples tested. All groups and samples presented peak release of unidentified substance of different molecular weight and different breaking time than the Bisphenol A standard. Additional researches using other analysis methods are needed to examine the cumulative estrogenic effects of Bisphenol A dental materials for CAD CAM and composite resins.